DEVELOPMENT OF INDONESIAN REALISTIC MATHEMATICS EDUCATION-BASED DIGITAL MODULE ON MATHEMATIC IN ELEMENTARY SCHOOL - Sri Suyanti; Rohana Rohana; Ali Fakhrudin (JIP Jurnal Ilmiah PGMI, 2021)
The development research aims to produce an Indonesian realistic mathematics education-based digital module on the Material of lowest common multiple (LCM) and greatest common factor (GCF) for Grade IV Elementary School (SD) which is valid, practical, and effective. In this research, the method used is research and development. The subjects in this study is students of class VI SD 247 Palembang, 25 student. The digital module developed using the ADDIE model; (1) Analysis (2) Design (3) Development, (4) Implementation, and (5) Evaluation. Data collection techniques is carried out with validation questionnaire sheet, response questionnaire sheets from students, and learning outcomes test. The results of data analysis is obtained that the first, digital module developed is very valid category based on the validation questionnaire from media expert, material expert, and linguists with an average validity value of 91.09%. The second, a digital module developed with a very practical category based on student’s response questionnaire with an average practicality value of 98.3%. The third, the digital module developed is very effective category based on the test result toward students by an average value of 84%. Based on the result of validation, practicality, and effectiveness, and test results, it can be concluded that the development of PMRI-based digital module on the LCM and GCF material for grade IV of elementary school can be used in mathematics learning.